MRI Manifestations in Isolated Ulnar Collateral Ligament Injury of the Thumb (Gamekeeper's Thumb) : A Systematic Review - Hafid Septian Nugroho; Anas Khoeruluman; Lely Sabariyah; Imam Mustika (International Medical Journal Corp. Ltd, 2026)
Introduction: Gamekeeper's thumb (acute ulnar collateral ligament injury of the thumb metacarpophalangeal joint) is a common sports-related injury. Accurate diagnosis, particularly differentiating Stener lesions from non-displaced tears, is critical for appropriate management. This systematic review synthesizes MRI manifestations and diagnostic performance for isolated thumb UCL injuries. Methods: A systematic literature screening identified studies involving living patients with isolated thumb UCL injury undergoing MRI evaluation. Data extraction focused on MRI techniques, imaging manifestations (ligament morphology, tear patterns, Stener lesions), diagnostic accuracy metrics, and classification systems. Results: The normal UCL demonstrates uniform hypointensity on all sequences with mean thickness 2.0-2.3 mm. Acute injuries show discontinuity, heterogeneous increased signal on fluid-sensitive sequences, and periligamentous edema. Distal insertion tears account for approximately 90% of ruptures. Partial tears demonstrate thickening (>7 mm) with <50% fiber involvement, while complete tears show full-thickness disruption. Stener lesions exhibit a characteristic